222 Investigating directionality of neurodegeneration in vivo in ALS using multimodal MRI. Issue 12 (14th November 2019) - Toh, Charmaine L; Keslake, Andrew; Harding, Joseph; Baster, Kathleen; Hoggard, Nigel; Bigley, Julia; McDermott, Christopher J; Shaw, Pamela J; Wilkinson, Iain D; Jenkins, Thomas M
Abstract : Background: The anatomical location of the earliest damage in amyotrophic lateral sclerosis (ALS) is still debated. Two main competing hypotheses have been proposed: the dying-forward hypothesis states the damage occurs in the precentral gyrus (PCG) and spreads caudally, which is in contrast with the dying-back hypothesis. This study aims to address this question of directionality of neurodegeneration in vivo using a multimodal neuroimaging approach to derive measures of damage of the motor pathway and analyse them in a common domain. Methods: MRI was performed on 78 ALS patients and 13 controls. PCG thickness was derived from using FreeSurfer, corticospinal tract (CST) fractional anisotropy (FA) from diffusion tensor imaging using FSL, and axial C3 cord area estimates using Philips online software. Comparisons between patients and controls were reported using unpaired t-tests. Parameter estimates were converted to z-scores, referenced to control data, plotted from PCG through CST to cord and directionality of damage assessed by fitting a mixed-effects linear regression model. Results: Z-scores were not significantly different between PCG and FA (0.24, [95%CI -0.13, 0.61], p=0.208) but were significantly lower in FA compared to cross-sectional cord area (-0.85, [95%CI -1.25, -0.46] p<0.001). Discussion: This novel multimodal imaging approach supports a dying-forward neurodegenerative process in ALS.